Development and validation of the parasocial relationships with religious figures scale - Dewanti, Yunita; Ifthiharfi, Ratu; Hamka, Muhammad Ahyar; Ruciswandaru, Ratriastu; Syarif, Akhmad Saputra; Seniati, Ali Nina Liche (INSPIRA: Indonesian Journal of Psychological Research, 2025)
The current study aimed to develop and validate the Parasocial Relationships with Religious Figures (PSR-R) scale, a multidimensional instrument designed to assess individuals' parasocial relationships with their idolized religious figures. A total of 301 participants aged 18–29 were recruited using convenience sampling, representing six religious groups in Indonesia. The scale development process involved item generation, expert evaluation, and confirmatory factor analysis to establish the structural validity of the scale. The final 25-item PSR-R scale demonstrated robust model fit (CFI = .908, RMSEA = .062, and SRMR = .607), capturing four dimensions: interest in, knowledge of, identification with, and interaction with. Internal consistency was high (? = .922), with dimension-level reliabilities ranging from .711 to .855 and significant intercorrelations among its four dimensions, supporting its validity as a multidimensional construct. Convergent validity was supported by a significant positive correlation with a measure of celebrity worship (r = .544, p < .001), suggesting that shared psychological processes underlie parasocial relationships across different domains. These findings support the PSR-R scale as a reliable and valid instrument for assessing parasocial relationships in religious contexts. By introducing a validated measurement tool, this study provides a foundation for further exploration of parasocial relationships with religious figures and their psychological implications. The scale offers theoretical and applied value for examining the psychological impact of mediated religious engagement. Future research should assess the cross-cultural generalizability of this approach, its role in identity development, and its potential applications in religious education, counseling, and mental health settings.